Professional Development of Project Management for Contractor in the Construction Project: A Review. (12th February 2015) - Rui, Lee Mao; Ismail, Syuhaida; Hussaini, Mohammad
Abstract: Professional development programmed can improve the effectiveness and capability of the contractor. A well organized development programme is a critical strategy for construction companies. In coming years, professional development was increasingly playing a significant role in organizational success. Based on the literature and previous research, the study explores the correlation professional development in employee training and motivation practices with task improvement in construction project. It is anticipated that the discussion of these factors will provide a basis for future strategies to promote the development of construction industry and also provide a useful reference for other industry which face similar problems in promoting the applications of professional construction project management in the construction industry. Professional development programmed had gone through the necessary project management training and sufficient knowledge, skills and experience to manage a project successfully.